Genome-wide diversity and admixture of five indigenous cattle populations from the Tigray region of northern Ethiopia - Zegeye, Tsadkan; Belay, Gurja; Vallejo-Trujillo, Adriana; Han, Jianlin; Hanotte, Olivier (Frontiers in Genetics, 2023)
The Tigray region, where we found around eight per cent of the indigenous cattle population of Ethiopia, is considered as the historic centre of the country, with the ancient pre-Aksumite and Aksumite civilisations in contact with the civilisations of the Fertile Crescent and the Indian subcontinent. Here, we used whole genome sequencing data to characterise the genomic diversity, relatedness, and admixture of five cattle populations (Abergelle, Arado, Begait, Erob, and Raya) indigenous to the Tigray region of Ethiopia. We detected 28 to 29 million SNPs and 2.7 to 2.9 million indels in each population, of which 7% of SNPs and 34% of indels were novel. Functional annotation of the variants showed about 0.01% SNPs and 0.22% to 0.27% indels in coding regions. Enrichment analysis of genes overlapping missense private SNPs revealed 20 significant GO terms and KEGG pathways that were shared by or specific to breeds. They included important genes associated with morphology (SCN4A, TAS1R2 and KCNG4), milk yield (GABRG1), meat quality (MMRN2 and VWC2), feed efficiency (PCDH8 and SLC26A3), immune response (LAMC1, PCDH18, CELSR1, TLR6 and ITGA5), heat resistance (NPFFR1 and HTR7) and genes belonging to the olfactory gene family, which may be related to adaptation to harsh environments. Tigray indigenous cattle are very diverse. Their genome-wide average nucleotide diversity ranged from 0.0035 to 0.0036. The number of heterozygous SNPs was about 0.6 to 0.7 times higher than homozygous ones. The within-breed average number of ROHs ranged from 777.82 to 1000.45, with the average sum of the length of ROHs ranging from 122.01 Mbp to 163.88 Mbp. The genomic inbreeding coefficients differed among animals and breeds, reaching up to 10% in some Begait and Raya animals. Tigray indigenous cattle shared a common ancestry with Asian indicine (85.6% to 88.7%) and African taurine (11.3% to 14.1%) cattle, with very small, if any, European taurine introgression. This study identified high within-breed genetic diversity representing an opportunity for breeding improvement programs and, also, significant novel variants that could increase the number of known cattle variants, an important contribution to the knowledge of domestic cattle genetic diversity.